2022
DOI: 10.2196/35595
|View full text |Cite
|
Sign up to set email alerts
|

Training Resources Targeting Social Media Skills to Inform Rehabilitation for People Who Have an Acquired Brain Injury: Scoping Review

Abstract: Background In 2020 and 2021, people increasingly used the internet to connect socially and professionally. However, people with an acquired brain injury (ABI) experience challenges in using social media, and rehabilitation professionals have reported feeling underprepared to support them in its use. To date, no review of social media skills training to inform ABI rehabilitation has been conducted. Objective This scoping review aimed to examine research … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 90 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…The finding that SLTs need to be adaptable may reflect a limited evidence base and a lack of ready-made therapeutic resources targeting a young person's social media use. Brunner et al (2022b) reviewed interventions and web-based resources targeting social media skills for both the general public and those with health conditions, particularly acquired brain injury (ABI). Just two of the 48 websites reviewed were tailored for children or young people, but neither were relevant or accessible for people with communication disability.…”
Section: Implications-including Future Directions For Researchmentioning
confidence: 99%
“…The finding that SLTs need to be adaptable may reflect a limited evidence base and a lack of ready-made therapeutic resources targeting a young person's social media use. Brunner et al (2022b) reviewed interventions and web-based resources targeting social media skills for both the general public and those with health conditions, particularly acquired brain injury (ABI). Just two of the 48 websites reviewed were tailored for children or young people, but neither were relevant or accessible for people with communication disability.…”
Section: Implications-including Future Directions For Researchmentioning
confidence: 99%
“…Potential neurorehabilitation support therefore extends to cyber safety training for people with ABI, with exploratory research indicating that more than half (n=54, 53.5%) of 101 surveyed Australian and New Zealand neurorehabilitation providers had clients who had been affected by cyberscams [ 25 ]. However, there is currently a lack of effective interventions supporting digital interactions through social media after ABI [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, people with TBI have reported receiving little professional support to use social media (Brunner et al, 2019) and rehabilitation professionals have described being inadequately prepared to support them in its use (Brunner et al, 2021b). A recent scoping review identified that, to date, there have been few interventions reported in the literature specifically addressing this area for people with ABI (Brunner et al, 2022b). There was limited evidence regarding the effectiveness of social media training, with Brunner et al identifying that social media training for people with ABI should be developed through user-centred design and evaluation (Brunner et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…A recent scoping review identified that, to date, there have been few interventions reported in the literature specifically addressing this area for people with ABI (Brunner et al, 2022b). There was limited evidence regarding the effectiveness of social media training, with Brunner et al identifying that social media training for people with ABI should be developed through user-centred design and evaluation (Brunner et al, 2022b). Many of the included social media skills training interventions and information sources incorporated or recommended training in aspects of cybersafety, opportunities for real-life practice and supports tailored to individual needs (Brunner et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation